Efficient carrier-reuse for intensity modulation and direct detection passive optical networks with Rayleigh backscattering noise circumvention - Zhang, Xiaoling (2018)
We propose an efficient carrier-reuse scheme for intensity modulation and direct detection (IM/DD) passive optical networks (PONs) with Rayleigh backscattering (RB) noise circumvention. In our proposed system, the number of light sources is halved since no extra light sources are required for the upstream (US) transmission, and the RB noise is eliminated without using any high cost ultra-narrow filter or coherent detection. The proposed scheme efficiently utilizes orthogonal frequency division multiplexing-based carrierless amplitude and phase modulation in the downstream, where signal multiplexing and demultiplexing are performed by digital filtering. Meanwhile, the high spectrum efficiency optical single-side band (SSB) Nyquist pulse-shaped pulse amplitude modulation-4 signal is generated by utilizing dual-drive Mach–Zehnder modulator in the US. In addition, the effect of phase-to-intensity conversion of the laser phase noise on bidirectional SSB systems over 25-km standard single-mode fiber on bit error rate performance is evaluated. Results successfully verify the feasibility of our proposed efficient carrier-reuse scheme for IM/DD PONs.